Coping mechanism among parents of children with autism spectrum disorder: a review - Al-Oran, Haytham; Lee, Khuan; Lim, Poh Ying; Hassouneh, Ola (Shahid Beheshti University of Medical Sciences (SBMU), 2022)
This review presented the current literature on coping mechanisms among parents of children with autism spectrum disorder (ASD), focusing on types of coping mechanisms among parents and different coping mechanisms between mothers and fathers of children with ASD. A search of published literature in English was conducted using Google Scholar, PsycINFO, Medline, Scopus, CINAHL, EBSCO, Springer, Ovid, PubMed, and Cochrane Library up to February 2020. Overall, 18 articles were relevant to the review. The review included thirteen studies for types of coping mechanisms among parents of children with ASD and five studies for different coping mechanisms between mothers and fathers. Coping mechanisms demonstrated by parents when caring for their child include problem-focused and emotion-focused coping. A comparison between fathers and mothers in our review showed that mothers used emotion-focused coping more than fathers, while fathers used problem-focused coping more frequently than mothers. The review provides an exciting opportunity to advance our knowledge on types of coping mechanisms and gender difference in using coping mechanisms among parents of children with ASD. The review also sheds new light on developing supportive interventions by healthcare providers to improve coping mechanisms among parents of children with ASD.